Subcutaneous Emphysema (Windpuff) in a 13 Weeks Old Pullet: Case Report - Kamani, J.; Tijjani, A.; Yidawi, J.P.; Gana, A.L.; Egwu, O.K.; Gusi, A.M. (International Journal of Poultry Science, 2009)
A known but rare condition of poultry and its management is being reported. The condition can be easily managed when notice early and treatment instituted on time. Simple use of needle puncture was able to relieve the condition a normalcy was achieved within a week.